PENGARUH JUMLAH KUNJUNGAN WISATA, OBJEK WISATA, DAN RESTORAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN/KOTA PROVINSI LAMPUNG TAHUN 2011-2020 - Evi Rahmawati, (2023)
Local own-source revenue has an important role in supporting local government funding sources to finance all regional operational and development needs, and other forms of public services. Therefore, to increase local revenue (PAD), the government must optimize which sectors can contribute. One of the efforts to increase local revenue is by optimizing the potential in the tourism sector. The tourism sector will contribute to local revenue (PAD) through tourist attraction fees and restaurant taxes. This research was conducted to determine the effect of the number of tourist visits, tourist attractions and restaurants on Regional Original Income (PAD) in the Regency/City of Lampung Province in 2011-2020. The data in this study is secondary data obtained through the Central Statistics Agency (BPS) and the Lampung Provincial Tourism Office. This study uses panel data regression analysis with the program used, namely Stata14 and uses hypothesis testing on a significance basis of 0.05 or 5%. The results of this study indicate (1) tourist visits have a significant influence on Regional Original Income in Lampung Province (2) tourist attractions do not have a significant influence on Regional Original Income (PAD) in Lampung Province (3) restaurants have a significant influence on Lampung Province Original Income . In addition, from this study it can be seen that the variable number of tourist visits, tourist attractions and restaurants has an effect on regional original income (PAD. Keywords: Number of Tourists, Attractions, Restaurants, Original Income